2014
DOI: 10.3109/17483107.2014.938705
|View full text |Cite
|
Sign up to set email alerts
|

Do people with intellectual disability use Nintendo Wii when placed in their home as part of a physiotherapy program? An observational study

Abstract: Usage of the Wii drops off rapidly when it is placed in the homes of people with intellectual disability as part of a physiotherapy program. Implications for Rehabilitation Usage of the Nintendo Wii drops off rapidly when it is placed in the homes of people with intellectual disability and they are instructed to use it as part of a home physiotherapy program. Games commonly played include bowling and boxing in Wii Sport, and penguin slide, ski jump and tight rope walk in Wii Fit Plus. Physiotherapists should u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Other studies on the efficacy of Wii games involved patients with multiple sclerosis, intellectual disability and Parkinson disease . The effect of virtual video games on children with CP has been demonstrated in some trials with small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on the efficacy of Wii games involved patients with multiple sclerosis, intellectual disability and Parkinson disease . The effect of virtual video games on children with CP has been demonstrated in some trials with small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on the efficacy of Wii games involved patients with multiple sclerosis, intellectual disability and Parkinson disease. [32][33][34][35] The effect of virtual video games on children with CP has been demonstrated in some trials with small sample sizes. 35 Six participants completed the study and it was concluded that Wii had the potential for use as a rehabilitation tool in the management of CP.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, predictability is an important facilitator for PA ( 74 76 ). In the scoping review by Lancioni et al ( 12 ) of stimulation-regulating technology to increase PA, one group of studies ( n = 15) used computer video games ( 77 , 78 ). The majority of the included studies ( n = 27) used sensors or other stimulation-regulating technology linked to computer systems or mobile technology to increase PA in the form of increased balance, stretching, and arm, leg, and head responses.…”
Section: Discussionmentioning
confidence: 99%
“… 118 , 119 , 120 , 121 , 122 , 123 Outcome(s): If there were no cognitive outcomes assessed, studies were excluded. 50 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 Study design: We excluded studies if they were not original articles but posters, 171 , 172 , 173 study protocols, 174 , 175 …”
Section: Methodsmentioning
confidence: 99%